2011
DOI: 10.3109/0886022x.2010.541579
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Silymarin and Vitamin E Supplementation on Oxidative Stress Markers, and Hemoglobin Levels Among Patients on Hemodialysis

Abstract: Background The incidence of accelerated atherosclerosis among patients on hemodialysis is very high and oxidative stress is a potentially major contributor to their morbidity and mortality. Objective To evaluate the effects of Silymarin and/or vitamin E on oxidative stress markers and hemoglobin level in patients on hemodialysis. Methods Eighty patients on hemodialysis were randomized into 4 groups: Group 1 received Silymarin 140 mg 3 times daily; Group 2 received Vitamin E 400 IU/day; Group 3 received Sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…The data indicate first that pretreatment in high-risk groups may have benefit in reducing IRI, but, in our opinion, these findings may be of relevance not only for I/R damage, but also for other conditions of kidney damage, including CKD. The rational supporting PEA action in CKD has been recently discussed in our review (Impellizzeri et al, 2014), while for silymarin extensive preclinical evidence and clinical data are already available (Fallahzadeh et al, 2012;Roozbeh et al, 2011). Since both agents are characterized by low toxicity, further work is warranted and we hypotetize that further studies will document the efficacy of the combination in other experimental models and in the clinical setting as well.…”
Section: Discussionmentioning
confidence: 91%
“…The data indicate first that pretreatment in high-risk groups may have benefit in reducing IRI, but, in our opinion, these findings may be of relevance not only for I/R damage, but also for other conditions of kidney damage, including CKD. The rational supporting PEA action in CKD has been recently discussed in our review (Impellizzeri et al, 2014), while for silymarin extensive preclinical evidence and clinical data are already available (Fallahzadeh et al, 2012;Roozbeh et al, 2011). Since both agents are characterized by low toxicity, further work is warranted and we hypotetize that further studies will document the efficacy of the combination in other experimental models and in the clinical setting as well.…”
Section: Discussionmentioning
confidence: 91%
“…According to the findings of previous studies, the supplementation procedure for silymarin was set at three 140 milligrams (mg) tablets per day (Roozbeh et al 2011). The experimental group received 140 mg silymarin supplement three times daily with main meals for 45 days.…”
Section: Methodsmentioning
confidence: 99%
“…Silymarin in rats with alloxan-induced diabetes mellitus significantly increase the activity of antioxidant enzymes such as SOD, GPX and catalase (CAT), and prevents renal tissue damage (Soto et al 2003(Soto et al , 2010. Oral supplementation of end stage renal disease patients with Silybum marianum (Livergol R ) extract and vitamin E led to a reduction of MDA and increases in red blood cell (RBC) GPX levels (Roozbeh et al 2011). Regarding the above-mentioned experimental studies (Soto et al 2003(Soto et al , 2010Wellington and Harvis 2001), silymarin potentially has antioxidant and anti-inflammatory characteristics; however, studies investigating the effects of silymarin on stress oxidative and inflammatory biomarkers have been limited to animal models and no clinical trials have been performed on diabetic patients.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Silymarin may exert positive effects in the management of patients with renal insufficiency. Recently, Roozbeh et al reported that treatment of hemodialysis patients with silymarin, alone or in combination with vitamin E, significantly decreased plasma MDA concentration and increased red blood cell glutathione peroxidase and hemoglobin levels (32). Silymarin also reduced kidney damage and restored activities of superoxide dismutase, glutathione peroxidase and catalase enzymes in rats with alloxan-induced diabetes (33).…”
Section: Discussionmentioning
confidence: 99%